Interacciones entre insectos y malezas en mono y policultivos de maiz y frijol - Altieri, Miguel A.; Doll, J.; Schoonhoven, Aart van (1977)
Tropical agroecosystems constitute diversified systems with crops arranged in polycultural patterns. Weeds are important components of these systems and condition insect diversity and stability. In an attempt to gather experimental evidence as a basis for tropical pest management strategies, 9 field and 2 laboratory experiments were conducted at CIAT (Palmira, Colombia). Two ecological strategies were proposed to change monoculture maize and bean pest susceptibility: polycultures and monocultures diversified with weeds. Weeds reduced adult nymph leafhopper (Empoasca kraemeri) populations 40 and 53 percent, respectively. Similarly, a maize/bean polyculture had 26 percent fewer adult leafhoppers than beans in monoculture. Weeds also decreased cutworm (Spodoptera frugiperda) damage to maize by 68 percent, while beans gave 38 percent reduction. The population of fall armyworm larvae was not affected by weeds but was reduced 23 percent in polycultures. Date of planting is an important factor affecting these interactions in polycultural systems. For example, maize planted 30 and 20 days before beans, reduced leafhoppers on beans